A national strategy for a low-carbon economy: The contribution of regional development planning. (March 2017) - Troy, Patrick
Planning for a low-carbon future in Australia will need to address simultaneously three aspects of sustainable development: centralisation/regional development, mobility and communication. After reviewing existing roadmaps for low-carbon growth by 2050, the article identifies the importance for Australia of an integrated and mutually reinforcing set of measures, based on a bold approach to urban and regional planning. Taking account of national geography, the approach is based on the decentralisation of energy production, use and storage, and on new uses of communication, transport and the location of food, water and mineral resources. Revitalised regional centres could be connected, through new energy and transport solutions, by a national transport arc and electrified highways. The use of infrastructure funding to support low-carbon regional development would avoid the 'tragedy of the commons', transcending incremental, cumulative approaches based on compensation and incentives for household, business and sectoral abatement efforts. It would generate long-term environmentally sustainable development.